The five people you meet in heaven [large type] - Albom, Mitch, 1958- (Hyperion, 2003)
"Eddie is a grizzled war veteran who feels trapped in a meaningless life of fixing rides at a seaside amusement park. Then, on his 83rd birthday, Eddie dies in a tragic accident, trying to save a little girl from a falling cart. With his final breath, he feels two small hands in his -- then nothing. He awakens in the afterlife, where he learns that heaven is not a lush Garden of Eden, but a place where your earthly life is explained to you by five people who were in it. These people may have been loved ones or distant strangers. Yet each of them changed your path forever. One by one, Eddie's five people illuminate the unseen connections of his earthly life."--Jacket.